Q: What is 6y 12 factored?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3y-6y in factored form = -3

Two ways to see this: 6y=8-9+6y 6y=6y-1 No answer here 6y= 8-(9+6y) 6y+(9+6y)=8 12y+9=8 12y=-1 y= -(1/12) or -0.08333...

3x + 6y = 12 Rearranging terms: 6y = -3x + 12 Divide through by 6: y = -1/2*x + 2

The slope of -x plus 6y is equals to 12 is said to be (2 + 1/6x).

16m-28m factored = -12

Related questions

3y-6y in factored form = -3

6y2 + 11y - 2 = (6y - 1) (y + 2)

It is: 2(x+3y) when factored

It is: (6y+1)(y-5) when factored

It is: 3y(2y-3x) when factored

-6y + 5 = -67y=12-6y = -72-y = -12y = 12

6y + 11 = 23 6y = 23 - 11 6y = 12 y = 12/6 y = 2.

It is a quadratic expression and is (2y-1)(3y-4) when factored

Two ways to see this: 6y=8-9+6y 6y=6y-1 No answer here 6y= 8-(9+6y) 6y+(9+6y)=8 12y+9=8 12y=-1 y= -(1/12) or -0.08333...

3x + 6y = 12 Rearranging terms: 6y = -3x + 12 Divide through by 6: y = -1/2*x + 2

6y2+17y-14 = (2x+7)(3x-2) when factored

y-3x+6y=12 7y=3x+12 y=3x/7 +12/7